The Effectiveness of Critical Evaluation and Questioning Techniques to Increase Students' Critical Thinking Skill: A Case Study - Espina, Jacqueline I. (Universitas Siliwangi, 2022)
This is a case study involving twenty-six (26) freshman Bachelor of Science in Social Work students of Leyte Normal University who are taking Purposive Communication in Semester 2, SY 2019-2020 as its subject. Based on the teacher-researchers observation and result of informal interviews with the students, they were generally quiet and seldom or never asked critical questions during class discussions because they were shy and did not know what questions to ask. It explored the effectiveness of Verderber, et al.’s critical evaluation and questioning techniques in enhancing critical evaluation and questioning behaviour or performance of the students, as well as its other positive impacts on them as students. The researcher has not encountered any studies that specifically utilized the said techniques. The intervention had positive results. Based on the students’ responses, their critical questioning behaviour or performance was improved in the sense that they learned to ask questions for clarification, to express contradiction or opposition, and to test the credibility of information and validity of the speaker’s contention. It also helped them transform into active learners, confident speakers, and critical thinkers. Hence, teaching students’ critical evaluation and questioning techniques can enhance their critical thinking skills and increase their engagement as well. Keywords: Critical thinking; Critical evaluation; Questioning techniques.